Dental Environment Stress and Students\' Personality in Rafsanjan Dentistry School - Zeinab Kazemizadeh; Hamid Bakhshi (مجله ایرانی آموزش در علوم پزشکی, 2011)
Introduction: Dentistry educational environment loads stress to the students.This can be harmful for educational system. The aim of this study was to investigate the stress perceived by the students in dentistry educational environment and the stress due to students' personality in Rafsanjan Dentistry School. Methods: In this cross- sectional study, the sample was selected from students of Refsanjan Dentistry school by census sampling in 2009. The Dental Environment Stress (DES) questionnaire was employed to assess perceived stress from dentistry environment, and the fourth part of Coudron stress questionnaire was used to investigate the stress due to students’ personality. Data were analyzed by ANOVA, Tukey post Hoc, T-test and Pearson's rank correlation. Results: Mean score of stress was 1.89± 0.54 (out of 4). The highest and the lowest perceived stress means were for the third (2.53± 0.25) and the first year students (1.54± 0.29) respectively. Among stressful domains, clinical work (2.39± 0.83) and personal factors (1.06± 0.53) had the highest and the lowest means, respectively. The highest stress mean was for completing clinical requirements (2.95± 1.06). There was no significant difference in environmental perceived stress between male and female students (P>0.05). Stressful personality was seen in 84.8% of students .There was no association between the means of DES and the students' stressful personality (r = 0.17, P = 0.05). Conclusion: The level of stress in Dentistry school is moderate with the highest level for clinical work. Although majority of dentistry students have stressful personality, it doesn't seem to increase the stress perceived by them due to dentistry environment. According to the highest level of stress in third year students, special interventions are recommended for this critical study year.